Analysis of Mathematical Reasoning Ability and Learning Obstacles Because of Gender on Social Arithmetic Topics - Sasmita Ramadani; Lisa Dwi Afri (Urogram Studi Pendidikan Matematika, Universitas IVET, 2023)
This study intends to explain how students' mathematical reasoning and learning obstacles in terms of gender are in the topic of social arithmetic. This exam employs a dazzling exploratory strategy. Information gathering was carried out, in this case, concentrating on the use of test kits and interviews. This exploration is directed at SMP IT Nurul Ilmi Jln. Pool, Medan Estate, Kec, Percut Sei Tuan with a total of six students consisting of three male subjects and three female subjects which were completed based on high, medium, and low thinking abilities. The side effect of the review showed that men's numerical thinking skills were better than women's numerical thinking skills. The learning obstacles experienced by men are epistemological, namely context limitations, students are not careful in solving test questions and ontogeny obstacles experienced are students' lack of mental readiness for learning and lack of mastery of the material. Meanwhile, the learning obstacles experienced by female students are epistemological and monogynous barriers. Epistemological barriers experienced occur due to limited context and low understanding of the material and they are also not careful and careful in understanding what is asked in the questions. The monogynous barriers experienced occurred because the students were not ready to follow the learning process. Keywords : Gender, Mathematical Reasoning Ability, Learning Obstacles, Social Arithmetic.